Exome Sequencing Identifies Potentially Druggable Mutations in Nasopharyngeal Carcinoma - Chow, Y.P.; Tan, L.P.; Chai, S.J.; Abdul Aziz, N.; Choo, S.W.; Lim, P.V.H.; Pathmanathan, R.; Mohd Kornain, N.K.; Lum, C.L.; Pua, K.C.; Yap, Y.Y.; Tan, T.Y.; et al. (Nature Publishing Group, 2017)
In this study, we first performed whole exome sequencing of DNA from 10 untreated and clinically annotated fresh frozen nasopharyngeal carcinoma (NPC) biopsies and matched bloods to identify somatically mutated genes that may be amenable to targeted therapeutic strategies. We identified a total of 323 mutations which were either non-synonymous (n = 238) or synonymous (n = 85). Furthermore, our analysis revealed genes in key cancer pathways (DNA repair, cell cycle regulation, apoptosis, immune response, lipid signaling) were mutated, of which those in the lipid-signaling pathway were the most enriched. We next extended our analysis on a prioritized sub-set of 37 mutated genes plus top 5 mutated cancer genes listed in COSMIC using a custom designed HaloPlex target enrichment panel with an additional 88 NPC samples. Our analysis identified 160 additional non-synonymous mutations in 37/42 genes in 66/88 samples. Of these, 99/160 mutations within potentially druggable pathways were further selected for validation. Sanger sequencing revealed that 77/99 variants were true positives, giving an accuracy of 78%. Taken together, our study indicated that similar to 72% (n = 71/98) of NPC samples harbored mutations in one of the four cancer pathways (EGFR-PI3KAkt-mTOR, NOTCH, NF-.B, DNA repair) which may be potentially useful as predictive biomarkers of response to matched targeted therapies.